Shakeup - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2020)
"Upon returning from a dangerous coastal adventure, Stone Barrington is looking forward to some normalcy with the leading lady in his life. But when a grisly crime arrives on his doorstep, along with some suspicious new clients eager for his help, Stone realizes peace and quiet are no longer an option. As it turns out, the mastermind behind the malfeasance rocking New York City and the nation's capital wields a heavy hand of influence. And when Stone is unable to recruit those closest to the case to his side, he is left with few leads and a handful of dead-ends. But with the help of important people in high places--and the expertise of alluring new friends--Stone is more than ready to rise to the occasion"--